The composition of the gut microbiota shapes the colon mucus barrier. (18th December 2014) - Jakobsson, Hedvig E; Rodríguez‐Piñeiro, Ana M; Schütte, André; Ermund, Anna; Boysen, Preben; Bemark, Mats; Sommer, Felix; Bäckhed, Fredrik; Hansson, Gunnar C; Johansson, Malin EV
Abstract Two C57BL/6 mice colonies maintained in two rooms of the same specific pathogen‐free (SPF) facility were found to have different gut microbiota and a mucus phenotype that was specific for each colony. The thickness and growth of the colon mucus were similar in the two colonies. However, one colony had mucus that was impenetrable to bacteria or beads the size of bacteria—which is comparable to what we observed in free‐living wild mice—whereas the other colony had an inner mucus layer penetrable to bacteria and beads. The different properties of the mucus depended on the microbiota, as they were transmissible by transfer of caecal microbiota to germ‐free mice. Mice with an impenetrable mucus layer had increased amounts of Erysipelotrichi, whereas mice with a penetrable mucus layer had higher levels of Proteobacteria and TM7 bacteria in the distal colon mucus. Thus, our study shows that bacteria and their community structure affect mucus barrier properties in ways that can have implications for health and disease. It also highlights that genetically identical animals housed in the same facility can have rather distinct microbiotas and barrier structures.